Antibody depletion therapy in transplantation: implications for tolerance - Turka, Laurence (Henry Stewart Talks, 2007)
Overview of alloreactivity, Tolerance approaches, Co-stimulatory blockade, Requirement for cell depletion, Homeostatic proliferation overview, Homeostatic proliferation generates memory cells and blocks tolerance induction, Depletion spares memory cells
Archived at 2021/02/25